Kinematic Analysis of Basketball Dribbling Movement In Grade VI Students of UPT SPF SD Negeri Paccinang - Hakim, Husni; Hudain, Muh. Adnan; Suwardi, Suwardi; Hakim, Hikmad; Bismar, Ahmad Rum (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to analyze the basketball dribbling ability of grade VI students of UPT SPF SD Negeri Paccinang through measuring kinematic parameters such as joint angle, movement speed, ball bounce height, and dribbling frequency. The approach used is quantitative with a survey method. The research sample consisted of 24 students who underwent a dribbling skills test. Data were taken through measurements using the Johnson Basketball Test instrument, which has a validity of 0.65-0.95 and a reliability of 0.84-0.97. Kinematic analysis was performed using Kinovea software to measure the position, speed, and acceleration of movement. The results showed significant variations in dribbling ability among students. For joint angles, 50% of students were in the poor category, while 45.8% were in the good category. Movement speed showed high consistency, with 91.7% of students in the moderate category. The number of students in the poor category in bounce height and dribbling frequency was 33.3% and 66.7%, respectively. This study found significant variations in ability among students, with movement speed as the most consistent parameter. Joint angles had the greatest variation, indicating the need for further attention in the development of students' dribbling techniques. This study emphasises the importance of a holistic approach in the development of basketball dribbling skills.